STRONGYLOIDIASIS IN GOATS - Корчан, Л. М.; Корнієнко, М. В. (Scientific Progress & Innovations, 2013)
The data concerning the incidence, age of strongyloidiasis dynamics in goats from individual farms in Lubny district, Poltava region (EI – 42 %, II – 147,2 eggs in 1 g of feces and 232,5 larvae in 5 g faeces), hematological changes and the effectiveness of anthelmintics macrocyclic lactones – ivermekvet 1 % and combination therapies – kombitrem and rafenzol for this invasion were investigated.